Topology Analysis and Modeling Comparison of SI-SIMO Boost Converter Used in Multiple Output Applications - Yilin Yan; Honghong Wang; Ping Ma; Jianquan Liao (Energies)
This paper presents the analysis and modeling of a single-input, single-inductor, multiple-output (SI-SIMO) boost converter to address limitations of conventional SISO converters in distributed power supply applications. Based on switching-state analysis, a sequential PWM modulation strategy is proposed to achieve independent voltage regulation across multiple outputs using a single inductor. An average circuit model is developed considering steady-state characteristics. Inductor conduction mode boundaries and the critical inductor value are derived. A complete modeling process is introduced, transitioning from nonlinear dynamics to small-signal approximation at the steady-state operating point. PSIM and MATLAB Simulink experiment results validate the proposed control method and confirm the theoretical analysis under various operating conditions.